Impact of Food Processing on Anthocyanins - Sui, Xiaonan (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2017)
This thesis studies the impact of food processing on the stability and antioxidant capacity of anthocyanins in aqueous and real food systems. It investigates the effects of temperature and pH on the stability and antioxidant capacity of anthocyanins in aqueous systems and in real semi-solid and solid food systems including bread and biscuits. The results of this thesis offer food manufacturers valuable guidelines on the production of functional foods containing anthocyanins, helping to reduce anthocyanins loss and achieve a desired amount of anthocyanins in foods with extra health benefits. .